Predictive model of socio-psychological factors of building confidence in the organization - Pochebut, L.G.; Gurieva, S.D.; Chiker, V.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2018)
The article presents the predictive model of socio-psychological factors of building confidence in the organization. In science still hasn’t determined the system factors of strengthening and maintaining trust. The article gives the classification of the basic conceptual approaches to the study of confidence in modern psychology: the psychological, socio-psychological, informational, subject-object. The main hypothesis is that the confidence of employees in the organization with balance the use of personas tactics interpersonal behavior. The study involved 149 people (40.5% of mane’s and 59. 5% women’s) aged from 25 to 45 years old, the staff of commercial organizations in St. Petersburg. Conducted testing and role playing game was obtained regression model predicting the confidence in the firm, identified the socio-psychological factors to enhance it (personal and group peculiarities, specific organizational culture), as the specific tactics achieve trust. The main conclusion is that establishing trust between people, based on their personal qualities, organizational culture and use of special tactics in business collaboration. В статье представлена прогностическая модель социально-психологических факторов укрепления доверия в организации. В науке до сих пор не определена система факторов укрепления и поддержания доверия. В статье дается классификация основных концептуальных подходов к изучению доверия в современной психологии, включающая психологический, социально-психологический, информационный, субъект-объектный подходы. Основная гипотеза исследования заключается в том, что укреплению доверия сотрудников к организации способствует применение особых тактик межличностного поведения. В исследовании участвовали 149 человек (40,5% мужчин и 59,5% женщин) в возрасте от 25 до 45 лет, сотрудники коммерческих организаций Санкт-Петербурга. Проводились анкетный опрос, тестирование и ролевая игра. Была получена регрессионная модель предсказания доверия в фирме, определены социально-психологические факторы его укрепления (личностные и групповые особенности, специфика организационной культуры), а также особые тактики достижения доверия. Основной вывод заключается в том, что установление доверительных отношений между людьми основано на их личностных качествах, организационной культуре и использовании особых тактик поведении в деловом взаимодействии.